Cochrane Database of Systematic Reviews 2004
DOI: 10.1002/14651858.cd003315.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Feeding interventions for growth and development in infants with cleft lip, cleft palate or cleft lip and palate

Abstract: Feeding interventions for growth and development in infants with cleft lip, cleft palate or cleft lip and palate. Cochrane Database of Systematic Reviews 2004 , Issue 3 . Art. No.: CD003315.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 54 publications
0
14
0
14
Order By: Relevance
“…Various methods of feeding cleft lip and palate babies have been investigated in previous studies to determine if weight gain and feeding efficiency could be improved 2,4,[9][10][11]13,14,17,19,22,23,25,29 . This aim of this study was to determine if syringe fed cleft babies gained more weight than those fed with cup and spoon and if feeding efficiency was improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods of feeding cleft lip and palate babies have been investigated in previous studies to determine if weight gain and feeding efficiency could be improved 2,4,[9][10][11]13,14,17,19,22,23,25,29 . This aim of this study was to determine if syringe fed cleft babies gained more weight than those fed with cup and spoon and if feeding efficiency was improved.…”
Section: Discussionmentioning
confidence: 99%
“…According to SHAW et al 25 , squeezable bottles were more satisfactory, requiring less intervention, resulting in an increase in weight of the cleft babies. GLENNY et al 10 found that squeezable bottles containing breast milk were easier to use and demonstrated a statistically significant difference in weight gain when compared with cup and spoon feeding. When this study is compared with those, it appears that it was also easier to use the syringe.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 The team nurse should provide the parents with information on feeding during prenatal counseling or immediately after birth. Initially, some children with cleft palate may show some discoordination of the "breathe, suck, swallow" reflex, resulting in nasal regurgitation of feeds or intermittent choking spells.…”
Section: Airway Evaluationmentioning
confidence: 99%
“…Treatment is often supplemented with aggressive orthodontic therapy until the maxilla and bones of the facial skeleton are grown completely. In some cases, a multidisciplinary approach is required to restore normal masticatory function and jaw movements during speech . Despite these efforts, the affected children, who have undergone surgical intervention, have also been shown to lack the means to provide adequate management of postoperative healing, pain, and infection, should they arise .…”
Section: Introductionmentioning
confidence: 99%